Should Firms Keep a Balance between State and Foreign Ownership? A Perspective on Financial Constraints and Investments in Vietnam - Gan, Christopher; Anh, Dao Le Trang (Asian Economic and Financial Review, 2019)
State and foreign ownership are increasing their role in financial management and performance of Vietnamese enterprises in the context of global and regional economic integration. Meanwhile, financial constraints and investments are two essential elements affecting corporate financial success. This study investigates the influences of governmental and foreign ownership on financial constraints and investment decisions of enterprises in Vietnam. Using regression models for panel data of 657 non-financial firms listed in Vietnam stock market, the study reveals that Vietnam listed firms with higher rates of state-owned shares exhibit higher levels of financial constraints. State ownership also restricts firms’ investments. On the other hand, foreign ownership helps to reduce the investment – cash flow sensitivity and enhances the firms’ investment levels. As a result, the study recommends that Vietnamese firms should try to eliminate the role and percentage of state ownership as well as attract more foreign investors to enhance the financial barrier and increase more promising investment opportunities to boost the firms’ financial outcomes.